A New Approach to Estimating the Sensible Heat Flux in Bare Soils - Francesc Castellví; Nurit Agam (Atmosphere)
The estimation of sensible heat flux (H) in drylands is important because it constitutes a significant portion of the net available surface energy. A model to estimate H half-hourly measurements for bare soils was derived by combining the surface renewal (SR) theory and the Monin–Obukhov similarity theory (MOST), involving the land surface temperature (LST), wind speed, and the air temperature in a period of half an hour, HSR-LST. The surface roughness lengths for momentum (<semantics>zom</semantics>) and for heat (z0h) were estimated at neutral conditions. The dataset included dry climates and different measurement heights (1.5 m up to 20 m). Root mean square error (<semantics>RMSE</semantics>) over the mean actual sensible heat flux estimate (HEC), E <semantics>=<mstyle scriptlevel="0" displaystyle="true">RMSE<mover accent="true">HEC¯</mover></mstyle>100%</semantics>, was considered excellent, good, and moderate for E values of up to 25%, 35%, and 40%, respectively. In stable conditions, HSR-LST and HMOST values were comparable and both were unacceptable (E > 40%). However, the RMSE using HSR-LST ranged between 8 Wm2 and 12 Wm2 and performed slightly better than HMOST. In unstable conditions, HSR-LST was in excellent, good, and moderate agreement in 3, 6, and 5 cases, respectively; HMOST was good in 3 cases; and the remaining 11 cases were intolerable because they required site-specific calibration.